Paraguay : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper describes economic developments in Paraguay during the 1990s. After recording a growth rate of 1.3 percent in 1996, real GDP expanded by 2.6 percent in 1997, or about the same rate as population growth. This reflected mainly a recovery in agricultural output owing to abundant rains. GDP growth suffered a new setback in 1998, with preliminary estimates showing a growth rate of only 0.6 percent, owing mainly to the continued stagnation in the manufacturing sector and a reduction of trade-related activities owing to tighter border controls in Brazil.